A novel halogen-free flame retardant poly (vinyl alcohol) foam with intrinsic flame retardant characteristics prepared through continuous extrusion. (March 2015) - Guo, Dan; Bai, Shibing; Wang, Qi
This paper reported a novel halogen-free flame retardant poly (vinyl alcohol) (PVA) foam with intrinsic flame retardant characteristics prepared through continuous extrusion using water as blowing agent. The morphology, cellular structure, mechanical properties and flame retardancy of the foams were systematically investigated. The experiments showed that PVA was not only the flame retardant target foam matrix, but also played an important role in char forming reactions, water not only acted as plasticizer and blowing agent for PVA thermal foaming, but also an effective synergistic flame retardant by evaporation to cool the system and suppress the point of inflammability, and melamine phosphate (MP) as halogen-free flame retardant was well dispersed in PVA matrix due to the strong interaction between MP and PVA, and also acted as excellent heterogeneous nucleating agent for foaming. The prepared halogen-free flame retardant PVA foam had good cellular structure, excellent flame retardancy and mechanical properties, i.e. apparent density 0.25 g/cm 3, average cell diameter 450 μm, cell density 10 3 cells/cm 3, reaching UL94 V-0, LOI 35%, tensile strength 1.8 MPa and elongation at break 57.1%. The novel halogen-free flame retardant PVA foam has potential applications.